13C-phenylalanine breath test and serum biopterin in schizophrenia, bipolar disorder and major depressive disorder. (April 2018) - Teraishi, Toshiya; Kajiwara, Masahiro; Hori, Hiroaki; Sasayama, Daimei; Hidese, Shinsuke; Matsuo, Junko; Ishida, Ikki; Kajiwara, Yasuhiro; Ozeki, Yuji; Ota, Miho; Hattori, Kotaro; Higuchi, Teruhiko; et al.
Abstract: Phenylalanine is required for the synthesis of the neurotransmitters dopamine, noradrenaline, and adrenaline. The rate-limiting step for phenylalanine metabolism is catalyzed by phenylalanine hydroxylase (PAH) and its cofactor tetrahydrobiopterin. We aimed to detect altered phenylalanine metabolism in major psychiatric disorders using thel -[1- 13 C]phenylalanine breath test ( 13 C-PBT) and serum biopterin levels. We also investigated association of PAH mutations with schizophrenia and phenylalanine metabolism. 13 C-phenylalanine (100 mg) was orally administered, and the breath 13 CO2 / 12 CO2 ratio was monitored for 120 min in four groups: 103 patients with schizophrenia (DSM-IV), 39 with bipolar disorder, 116 with major depressive disorder (MDD), and 241 healthy controls. Serum biopterin levels were measured by high performance liquid chromatography. Mutation screening of PAH exons was performed by direct sequencing in 46 schizophrenia patients. Association analysis was performed using six tag single nucleotide polymorphisms and the PAH Arg53His mutation by TaqMan assays in 616 schizophrenia patients and 1194 healthy controls. Analyses of covariance controlling for age, sex, and body weight showed that the index for the amount of exhaled 13 CO2 was significantly lower in the schizophrenia group than in the other three groups (all p < 0.05). Biopterin levels in schizophrenia and MDD were significantly lower than those in controls. Biopterin levels correlated with 13 C-PBT indices in controls. PAH polymorphisms were not associated with schizophrenia or 13 C-PBT indices. 13 C-PBT revealed reduced phenylalanine metabolism in schizophrenia, though we obtained no evidence of involvement of PAH polymorphism. Serum biopterin levels were lower in schizophrenia and MDD, warranting further investigation.